Plant extracts carboxylic acids and soil humidity influence production and cracking of cape gooseberry (Physalis peruviana L.) fruit (2011)
In order to reduce the percentage of fruit cracking and increase size and weight of cape gooseberry fruits, the effect of carboxylic acids contained in the product Carboxy® Calhard (poly-hydroxy-carboxylic acids [78 g∙L-1], complemented with calcium and boron), was studied in a commercial crop. Product doses of 0, 1.5 and 3.0 L∙ha-1 and three levels of soil humidity: 10-25%, 25-50% and 50-75%, were used. The treatments 0, 1.5 and 3.0 L∙ha-1 of Calhard at 50-75% of soil humidity resulted in a higher percentage of exportable fruits, 40.17, 41.67 and 45.33% respectively, as well as the lowest number of fruits for the national market (31.33, 29.67 and 37.0%, respectively) due to the high soil humidity. The treatments 0 and 1,5 L∙ha-1 Calhard at 50-75% of soil humidity showed the highest percentage of cracked fruits, 28.50 and 28.67% respectively, whereas 3 L∙ha-1 of Calhard at 50-75% soil humidity reduced significantly the percentage of cracked fruits to 17.67% due to application of carboxylic acids. Fresh fruit weight without calyx was related to the product dose and soil humidity, showing the treatment 3.0 L∙ha-1 of Calhard at 50-75% of soil humidity as the one with the highest fresh fruit weight (4.04 g) compared to the control (3.58 g). Calhard application of 1.5 and 3.0 L∙ha-1 increased the equatorial diameter of fruits with values of 18.56 and 18.95 mm respectively, while 0 L∙ha-1 Calhard and the control showed the less fruit diameter values (18.39 mm).